THE PHENOMENON OF POLITICIZATION OF CHESS IN THE SOVIET UNION - Evgeny Alekseevich Levin (Sovremennye Issledovaniâ Socialʹnyh Problem, 2016)
This article tells about the phenomenon of politicization of chess in the Soviet Union. It is analyzed about key moments and periods of chess history of the Soviet Union, with participation of country’s political government. The main purposes of this article, are tracing of the main stages in the development of chess in the USSR, also to determine the degree of intervention of political power in chess sport, and the role of sport as a resource for managing the external and internal political processes. This parts of political and historical science are poorly known nowadays. The article tells about a number of same example. It is attentively analyzed about the period of Cold War Particularly given the impact of chess-political confrontation between the USSR and the West during the Cold War. As one of the main conclusions, it is denoted about negative sides of the politicization of chess in the Soviet Union and also positive sides.